Training of AI systems in the healthcare sector: interactions between the general data protection regulation and the artificial intelligence act - Zouak Lara, Paola (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The training of artificial intelligence systems in the healthcare sector raises complex regulatory interactions between the General Data Protection Regulation (GDPR) and the Artificial Intelligence Regulation (AI Act). While the GDPR strictly governs the processing of personal data, the AI Act primarily sets requirements for high-risk systems, a category that includes many healthcare applications. This regulatory convergence demands a thorough assessment of the scope of both instruments, a technical understanding of AI training processes, and a balanced approach that ensures both the protection of fundamental rights and responsible technological innovation in the health sector.